Patterns of Failure in Patients With Advanced Non-Small Cell Lung Cancer Treated With Immune Checkpoint Inhibitors - Chai, Rong; Yin, Yipengchen; Cai, Xuwei; Fu, Xiaolong; Zhang, Qin (Frontiers in Oncology, 2021)
Objective The advent of immune checkpoint inhibitors (ICIs) has rapidly transformed the treatment paradigm of non-small cell lung cancer (NSCLC). Despite the durability of response to ICIs, the vast majority of patients will later develop progression. However, the failure patterns of ICI treatment are unknown. Here, our study explored the failure patterns in advanced NSCLC patients treated with ICIs. Methods A cohort of 156 IIIB or IV NSCLC patients treated with first-/second-line ICIs were retrospectively analyzed. Patients who experienced clinical benefit and then developed progression were identified. The disease progression patterns were divided into three categories: progression in new sites, progression in existing sites, and combined progression. The number of progression sites was also recorded. Results Before the cutoff date, 91 (77.1%) patients had experienced disease progression; 34% of patients had progressed in the last 9 months of the first year. Fifty-three (58.2%) patients had developed progression at existing lesions, and 56 (61.5%) patients had shown ≤2 progression sites (oligo-progression). In patients with oligo-progression, the median time of disease progression was 8.23 months and the counterpart (systemic progression) was 5.97 months. The oligo-progression patients showed prolonged median overall survival (27.23 months) compared with patients with systemic progression (18.87 months). Conclusions Failure patterns of ICI therapy were predominantly “existing” sites, and the most common lesions of progression were the lung and lymph nodes. Most patients experienced oligo-progression which occurred later than systemic progression and showed prolonged overall survival. The control of the local lesions might be beneficial to improve ICI treatment efficacy.